Analysis of visual impact by new building height through UAVs and photogrammetry - Gutiérrez-Peña, Javiera; Herrera, Rodrigo F.; Atencio, Edison; Muñoz-La Rivera, Felipe (Journal of Civil Engineering and Management, 2024)
Visual impact is defined as the modification of a visual resource of the landscape, generating an effect on the perception of potential observers. This effect is evaluated using the value of the landscape that has not been altered or destroyed (visual quality of the landscape), as is the case with building projects that generate visible changes in residential areas. Numerous authors have developed methodologies to evaluate visual intrusion; however, deficiencies exist, such as the predominance of subjectivity in procedures and the lack of evaluations for buildings. Therefore, this paper proposes a methodology to evaluate and quantify the visual impact of a new building in a high population density environment. This research is divided into a description of the basic methodology, the proposal of the methodology to capture and process photographs and information, and the application of a case study of a high-rise building in a sector of Valparaíso, Chile. The main contribution of this work is the delivery of a methodological proposal that allows the evaluation and quantification of the visual quality before and after the new structure to complement structural and urban design.